2003
DOI: 10.1189/jlb.0502243
|View full text |Cite
|
Sign up to set email alerts
|

The role of CCL22 (MDC) for the recruitment of eosinophils during allergic pleurisy in mice

Abstract: Eosinophils are important inflammatory cells in allergic diseases. In the present study, we have investigated the effects of CCL22 on the recruitment of eosinophils in vivo and in vitro. CCL22 induced a dose- and time-dependent recruitment of eosinophils into the pleural cavity of mice, and this was dependent on the release of platelet-activating factor (PAF) and subsequent generation of CCL11. However, in an allergic pleurisy model, an anti-CCL22 polyclonal antibody given during sensitization or before challe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
19
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 36 publications
3
19
0
Order By: Relevance
“…On the other hand, RANTES failed to elicit eosinophil migration. These results indicate that mouse eosinophils prepared by this method are functionally comparable to previously reported mouse eosinophils in terms of migration activity [25], and that at least CCR3 and PAF receptors expressed on these eosinophils were functional.…”
Section: Migration Of Mouse Eosinophils In Response To Eotaxin and Pasupporting
confidence: 83%
See 2 more Smart Citations
“…On the other hand, RANTES failed to elicit eosinophil migration. These results indicate that mouse eosinophils prepared by this method are functionally comparable to previously reported mouse eosinophils in terms of migration activity [25], and that at least CCR3 and PAF receptors expressed on these eosinophils were functional.…”
Section: Migration Of Mouse Eosinophils In Response To Eotaxin and Pasupporting
confidence: 83%
“…As shown in Figure 1B, almost all of the cells purified mouse eosinophils expressed CCR3, which has been used as eosinophil markers in peripheral blood cells from IL-5 TG mice [4]. The confirmation of eosinophil functions indicated that these cells were comparable to Schistosoma mansoni-infected mice derived [25] or human [1] eosinophils, in terms of eotaxin-induced chemotaxis. In addition, RANTES, which can bind to CCR1, CCR3 and CCR5 [32], had no significant effect on the migration of mouse eosinophils in vitro (Fig.…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Although it is not know whether either chemokine directly activates pulmonary fibroblasts to generate collagen, both chemokines have been shown to regulate the movement of eosinophils into the lung. 18,19 Human 70 and mouse 71 eosinophils express CCR4 particularly during an allergic inflammatory response, and these cells have been implicated in experimental and clinical fibrotic responses in the lung. 72 In the present study, we observed that the immunoneutralization of either CCL17 or CCL22 significantly reduced the eosinophilia associated with the egg granuloma.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, it has been reported that CCR4 and its ligands are able to modulate innate immune responses (17,18). A potential role for CCL22 in Treg function has been suggested by the observation that in breast tumors producing CCL22, infiltrating Tregs are characterized by higher activation status and proliferation rate (5).…”
mentioning
confidence: 99%